KEANEKARAGAMAN IKAN KARANG DI PERAIRAN REBO SUNGAILIAT, BANGKA - Sastra Apriza; Wahyu Adi; Eva Utami (Akuatik: Jurnal Sumberdaya Perairan, 2016)
Reef fish are organisms that live in reef area. Their life depend on coral reef condition the purpose of the research are to know diversity and abundance of reef fish, to know coral lifeform percentage, to describe the association of coral reef fish and to know chemical. The research was done in June 2015. The method used is Belt Transect. Data analysis includes diversity index, uniformity, dominance, species composition, species abundance, relative density, frequency of attendance, lifeform percentage and association of reef fish with coral reef. Diversity index of Karang Rulak is 2,329 and Karang Kering is 1,711. Uniformity index of Karang Rulak is 0,908 and Karang Kering 0,879. Dominance index of Karang Rulak 0,113 and Karang Kering is 0,209. Reef fish that found in Karang Rulak are 13 species and Karang Kering are 7 species. The highest of Reef fish abundance in Karang Rulak is Cephalopholis boenak that 55 individual/300m2 and the lowest is Acanturidae that 2 individual/300m2. The highest of Reef fish abundance in Karang Kering is Pentapodus sp that 45 individual/300m2 and the lowest is Abudefduf sexfasciatus that 4 individual/300m2. The cover lifeform percentage in Karang Rulak is 69,91% and Karang Kering is 24,57%.